Gut microbiota in systemic lupus erythematosus patients and lupus mouse model: a cross species comparative analysis for biomarker discovery - Toumi, Eya; Goutorbe, Benoit; Plauzolles, Anne; Bonnet, Marion; Mezouar, Soraya; Militello, Muriel; Mege, Jean-Louis; Chiche, Laurent; Halfon, Philippe (Frontiers in Immunology, 2022)
Increasing number of studies have provided strong evidence that gut microbiota interacts with the immune system and stimulates a variety of mechanisms involved in the pathogenesis of auto-immune diseases such as Systemic Lupus Erythematosus (SLE). Indeed, gut microbiota could be a source of diagnostic and prognostic biomarkers but also hold the promise to discover novel therapeutic strategies. So far, specific SLE microbial signatures have not yet been clearly identified with alteration patterns that may vary between human and animal studies. In the present study, a comparative analysis of clinically well-characterized cohort of adult SLE patients showed a reduced biodiversity, a lower Firmicutes/Bacteroidetes (F/B) ratio and six differentially abundant taxa compared to healthy controls. An unsupervised clustering of SLE patients identified a subgroup of patients with a stronger alteration of their gut microbiota. Interestingly, this clustering was strongly correlated with the disease activity assessed with Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score (p=0.03, odd ratio =15) and the identification of specific alterations involving the F/B ratio and some different taxa. Then, the gut microbiota of pristane-induced lupus mice and control mice were analyzed for comparison with our human data. Among the six differentially abundant taxa of the human disease signature, five were common with our murine model. Finally, an exhaustive cross species comparison between our data and previous human and murine SLE studies revealed a core-set of gut microbiome species that might constitute biomarkers panels relevant for future validation studies.